Physics of road cycling and the three jerseys problem. (8th March 2021) - Cohen, Caroline; Brunet, Emmanuel; Roy, Jérémy; Clanet, Christophe
Abstract: Abstract : Tour de France, Giro d'Italia and Vuelta a España in Spain are the three grand tours of professional road cycling. Three weeks long with daily stages, these three races all use three jerseys to distinguish the leader, the best sprinter and the best climber. We first discuss the physics of road cycling and show that these three jerseys are associated with three different dynamical regimes. We then propose a phase diagram for road cycling which enables us to discuss the different physiological characteristics observed in the peloton. We finally establish the phase diagram for the Tour de France 2017 and show that the final three jerseys do belong to the expected three optimal regions of the phase diagram.